Modified acupuncture therapy, long-term acupoint stimulation versus sham control for weight control: a multicenter, randomized controlled trial - Dai, Liang; Wang, Miao; Zhang, Ke-Pei; Wang, Lin; Zheng, Hui-Min; Li, Chun-Bo; Zhou, Wen-Jun; Zhou, Shi-Gao; Ji, Guang (Frontiers in Endocrinology, 2022)
Objective Long-term acupoint stimulation (LAS), also called embedding acupuncture, is a modified acupuncture technique. The preliminary results have demonstrated its efficacy in body-weight control. However, the low quality of available trials limited its application. This study aimed to evaluate the efficacy and safety of LAS in body-weight control by using a randomized, parallel, sham-controlled clinical trial design. Methods This was a randomized, single-blind, sham-controlled clinical trial including 84 adult participants (18–60 years) with a body mass index (BMI) of ≥ 24 kg/m2 conducted in three general hospitals in Shanghai, China. Participants were equally assigned to receive LAS or sham LAS (SLAS) once per 10 days, eight times in total. After completion, an additional intervention with a 3-month follow-up period was set to examine the continued effect of LAS. The primary outcome was the change in body weight from baseline to treatment endpoint within the intention-to-treat (ITT) analysis. Secondary outcomes contained changes in waist-to-hip ratio (WHR), lipid metabolism, and visceral and subcutaneous adipose tissues. Results From 14 May 2018 to 03 November 2019, 84 participants out of 201 screened individuals met the eligibility criteria, were randomized, and were analyzed (42 participants in each group). From baseline to treatment endpoint, the body-weight reduction in the LAS group was significantly larger than in the sham control (net difference: 1.57 kg, 95% CI: 0.29–2.86, p = 0.012). The superior weight reduction effect persisted in the follow-up period (net difference: 3.20 kg, 95% CI: 1.17–5.21, p = 0.001). LAS therapy also showed improvement in triglyceride and subcutaneous adipose tissue (SAT) compared with sham control. One participant in the LAS group reported a slightly uncomfortable and tingling sensation after the additional intervention. No other adverse events (AEs) were documented. Conclusion LAS, a modified acupuncture technique, is safe and effective in body-weight control. It could be used as an alternative choice to classical acupuncture for obesity management. Clinical Trial Registration [www.chictr.org.cn], identifier [ChiCTR1800015498].